Utilizing Rice Hull Ash and Biomass as Ameliorants Enhanced Soybean Yield and Nutrient Uptake in Tidal Swamps Under Saturated Soil Culture - Toyip, Toyip; Ghulamahdi, Munif; Sopandie, Didy; Aziz, Sandra Arifin; Sutandi, Atang; Jarwadi Purwanto, Mohamad Yanuar (PLANTA TROPIKA, 2024)
Saturated soil culture (SSC) is a promising technology for cultivating soybeans in acidic soil in tidal swamps. The objectives of this study were to measure nutrient uptake in the soybean plant using a saturated soil culture technique and to assess the impact of ameliorant addition in the form of rice biomass and rice hull on soybean yield. Two factors, rice biomass, and rice hull ash, were used in a split plot factorial design to set up the experiment. Four levels in the main factor included without biomass immersion, one immersion of short (3 cm above the root) rice stubble, one immersion of regular (panicle harvested only) rice straw, and two immersions of regular rice straw cut in the soil. The four levels in the subfactor were 0 t ha-1, 0.25 t ha-1, 0.50 t ha-1, and 0.75 t ha-1 of rice hull ash doses. Ameliorant in the form of biomass and rice husk increases soil quality in tidal swamps by enhancing pH, soil nutrients (N, P, K, S), CEC, cations, and base saturation, also reducing toxic compounds and improving soil texture. Application of ameliorant also increases soybean nutrient uptake and eventually increases the productivity of soybeans in tidal swamp acid soil. The best treatment of the first and second factors was one immersion of biomass with a regular cut of rice straw and 0.5 t ha-1 ash rice hull ash addition to the tidal swamp soil, respectively.